Per-Vaginal Delivery of Dicephalic Perosomus Elumbis Monster by Partial Fetotomy in a Cow - Panihar, Sandeep; Pandey, Anand Kumar; Pradeep; Singh, Gyan; Kumar, Rakesh; Garbhit (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Dystocia, a challenging condition in obstetrics, can arise from various causes, including fetal monsters with structural abnormalities. Congenital fetal monstrosities are not uncommon clinical findings in dairy cattle where multiple anatomical defects could be found in the fetal monsters. Although, the exact etiologies for these conditions are not known but their clinical presentation sometimes causes life threatening condition to the dam along with the loss of calf crop. The most common group of monsters is conjoined twins which arise from incomplete division from fertilized ovum. Dicephalic is described as an abnormality of incomplete separation of heads resulting from twinning in animals. Perosomus elumbis is a rarely occurring congenital condition characterized with partial or complete agenesis of lumbar, sacral and coccygeal vertebrae and ankylosis of hind limbs (Son, 2008). The conspicuous feature for the obstetrician is the rigidity of the posterior limbs (Arthur et al., 2001). Double headed calf represent a case of absolute fetal oversize with subsequent provoke of dystocia in animals. The present report represents the successful per-vaginal delivery of dicephalic perosomus elumbis monster by partial fetotomy in a cow.